Rethinking Global Health Frameworks of Power - Burgess, Rochelle A. (Critical Approaches to Health, 2024)
This book reflects and analyses the working of power in the field of global health- and what this goes on to produce. In so doing, Rethinking Global Health asks the pivotal questions of, 'who is global health for' and 'what is it that limits our ability to build responses that meet people where they are?' Covering a wide range of topics from global mental health to Ebola, this book combines power analyses with interviews and personal reflections spanning the author's decade-long career in global health. It interrogates how the search for global solutions can often end up far from where we anticipated. It also introduces readers to different frameworks for power analyses in the field, including an adaptation of the 'matrix of domination' for global health practice. Through this work, Dr Burgess develops a new model of Transformative Global Health, a framework that calls researchers and practitioners to adopt new orienting principles, placing community interests and voices at the heart of global health planning and solutions at all times. This book will be beneficial to students and academics working in the global and public health landscape. It will also hold appeal to activists, practitioners and individuals invested in the discipline and in health equity around the world.